(untitled) (Texas Journal of Medical Science, 2021)
Tennis elbow, also known as lateral epicondylitis, refers to a degenerative condition affecting the common origin of the forearm’s extensor muscles & is a rather frequent ailment for which individuals seek therapy. It’s a condition that significantly limits a person’s function and movement, necessitating many visits to orthopedic specialists each year. The main symptoms were continuous discomfort and soreness around the lateral epicondyle, as well as an inability to perform everyday tasks & and it is most prevalent in the fourth and fifth decades of life. Rest, bracing, prescription of nonsteroidal anti-inflammatory medications, physiotherapy, and extracorporeal shock wave therapy are among conservative therapeutic options. Corticosteroid injections and regeneration injections are two more conservative treatment approaches. The injections are used to postpone and/or eliminate the need for surgery. The use of endogenous growth factors in LE therapy has shown encouraging outcomes in vitro and in vivo, because to advances in molecular biology and regenerative medicine. The aim of this study is to evaluate the PRP local injection for the treatment of LE in terms of safety and efficacy